Volunteering in higher education as a basis for teacher professional development - Vasileva, Aitalina Nikolaevna (2020)
The purpose of this paper is to define the role of volunteer activities in the professional development of future teachers who are currently students attending higher education institutions. The main research method used in this work is descriptive and qualitative, since analyze a number of volunteer students in the Pedagogical Institute at Ammosov North-Eastern Federal University (Sakha, Russia) on the basis of results of annual NEFU sociological research for the period 2017-2019 and examining their motivation for volunteering through a survey. Students volunteered in a wide range of activities: educational programs, academic practical training, preparation of scientific papers, and implementation of socially significant projects. When the pedagogical university students arranged their volunteer activities to relate to their future professional activities, they significantly broadened their knowledge about the chosen profession, reinforced their motivation for professional development, and generated adequate self-assessments of their personal and professional qualities as future teachers. In conclusion: professionally oriented volunteer activity as part of educating future teachers develops not only the required professional qualities and competencies but also becomes a stage of their professionalization, helping them to find their place of employment faster and developing their social and professional skill sets. The practical implications of the study lie in the possibility of using the research results to arrange volunteer activities at universities.